Analisis Literasi dan Rasional Ekonomi Masyarakat Dalam Memanfaatkan Jasa Simpan Pinjam Lembaga Keuangan Informal - Dwi Yanuarindah Putri; Fidyah Jayatri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Economics is one of the challenges humans faces in everyday life, especially in meeting their needs. Humans must meet all their complex needs to survive. Economic behavior is a measure of societal behavior, especially family economics. To avoid economic problems within the family, people often choose to use credit services from loan shark. Due to various factors behind people's savings and loans, they agree to pay high interest rates as long as they can meet their needs. This study used a qualitative narrative approach. This study involved five informants, consisting of savings and loan service users and third parties. The research findings showed that the Kalidilem community borrowed money from loan shark without their partners' knowledge, and that the proceeds were mostly used for personal needs, not for starting businesses. The level of economic literacy and rationality of the Kalidilem community is relatively low because they still do not understand the concepts and indicators of economic literacy and rationality and are still unable to utilize legal financial services, which impacts the family economy.